2022
DOI: 10.1186/s12886-022-02638-x
|View full text |Cite
|
Sign up to set email alerts
|

A moderate dosage of coffee causes acute retinal capillary perfusion decrease in healthy young individuals

Abstract: Aim: Caffeinated beverages are very popular across populations and cultures, but quantitative evidence of the acute effects of moderate coffee doses on retinal perfusion is sparse and contradicting. Thus, the aim of this randomized, cross-over and parallel-group design study was to investigate whether moderate consumption of coffee alters macular retinal capillary perfusion in young healthy individuals. Methods: Twenty-seven young healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ASL is used to evaluate the tissue perfusion rate. Tissue perfusion—the exchange of water and nutrients with tissues—occurs over the entire length of capillaries (Zhu et al, 2022 ). ASL basically “tracks” the water molecules in the blood from the arterial cavity to the tissue capillary bed and treats the water molecules as a freely diffusible tracer.…”
Section: Discussionmentioning
confidence: 99%
“…ASL is used to evaluate the tissue perfusion rate. Tissue perfusion—the exchange of water and nutrients with tissues—occurs over the entire length of capillaries (Zhu et al, 2022 ). ASL basically “tracks” the water molecules in the blood from the arterial cavity to the tissue capillary bed and treats the water molecules as a freely diffusible tracer.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged uncontrolled hyperglycemia could cause severe ocular microvascular abnormalities and loss of the blood-retinal barrier 54 . Randomized controlled trials have demonstrated that daily dose coffee consumption leads to acute reductions in macular retinal capillary perfusion and cerebral circulation 55 , and that caffeine intake could induce microvascular constriction in ophthalmology 56 . In addition, coffee could affect the development of diabetic ocular complications through changes in intraocular structures such as intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%